A banner bearing the name of the temple in Devanagari script - Mumbai Archive Project Team (Jio Institute, 2024)
A banner bearing the name of the temple in the Devanagari script obscures the view of an elevated platform with the goddess Durga as Mahishasurmardini (slayer of Mahishashura).